Le néocriticisme d’Henri Bois et ses conséquences missiologiques - Mino Randriamanantena (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
His philosophy, inspired of the French neocriticism, led Henri Bois to study and to meet non christian religions. Our contribution proposes to expose how the thought of Henri Bois evolves in contact with those. Coming from the evangelic (or orthodoxe) part of the Protestantism of the time, which tends to exclude any religion apart from Jesus Christ, Henri Bois, by the importance which he attaches to the moral conscience and the achievement of the moral and religious ideal in Jesus, skin progressively his christology, involving a considerable evolution on the level of his understanding of the Mission.